THE IMPLEMENTATION OF THE ONE-STOP SERVICE (PTSP) POLICY TO IMPROVE THE SERVICE QUALITY AT THE MINISTRY OF RELIGIOUS AFFAIRS OFFICE IN GORONTALO - Thalib, Nurhairatnie; Ilato, Rosman; Abdussamad, Juriko (Universitas Negeri Gorontalo, 2020)
This research aims to 1) analyze and describe the implementation of the One-stop Service (PTSP) policy to improve the service quality at the Ministry of Religious Affairs Office in Gorontalo, 2) analyze and describe the supporting factors of the implementation of one-stop service (PTSP) to improve the quality of religious education and religious affairs services at the Ministry of Religious Affairs Office in Gorontalo, and 3) analyze and describe the inhibiting factors of the implementation of the One-stop Service (PTSP) policy to improve the quality of religious education and religious affairs services at the Ministry of Religious Affairs Office in Gorontalo. The research method used is qualitative-descriptive; while the research location is the Ministry of Religious Affairs Office in Gorontalo. The data collection techniques are observation, interview, and documentation. The descriptive data are analyzed using Miles and Huberman’s theory with the approaches i.e. 1) data reduction and simplification, 2) data presentation, and 3) conclusion drawing. This research clarifies that the implementation of the One-stop Service (PTSP) policy in the Ministry of Religious Affairs Office in Gorontalo is conducted by the plan and procedures following SOP and KMA No. 90/2018. Some improvements are made through regular evaluations of target achievement, supporting power, and challenges. Institutional and technical supporting factors are crucial for the implementation of One-stop Service (PTSP). Among the inhibiting factors found are a lack of resources, a lack of public awareness of operational service standards, the level of activity of the officials in charge of the legality of the document, and a limited budget. The corrective actions are adjusting the service provision to the allocated budget, giving socializations regarding the service procedures via printed and audio media, conducting verbal communication, and mapping and proffering the fulfillment of budget by considering the priority scale.